2018
DOI: 10.1007/s11695-018-3128-9
|View full text |Cite
|
Sign up to set email alerts
|

Conversional Weight Loss Surgery: an Australian Experience of Converting Laparoscopic Adjustable Gastric Bands to Laparoscopic Sleeve Gastrectomy

Abstract: We therefore conclude that sleeve gastrectomy is a safe and valid option for conversional bariatric surgery following LAGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Several studies have shown that conversion to another bariatric procedure is safe with low morbidity (1.1%) and mortality (<1%) [24,25]. Both conversion procedures have similar complication rates, hospital stay and early weight loss [22][23][24][25]. Additionally, the EWL in converted patients at two years was similar, approximately 60% [22,25].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies have shown that conversion to another bariatric procedure is safe with low morbidity (1.1%) and mortality (<1%) [24,25]. Both conversion procedures have similar complication rates, hospital stay and early weight loss [22][23][24][25]. Additionally, the EWL in converted patients at two years was similar, approximately 60% [22,25].…”
Section: Discussionmentioning
confidence: 95%
“…For patients requiring reintervention and seeking further weight loss after LAGB failure, conversion to LSG or LRYGB in a one-or two-stage procedure is feasible [22][23][24][25]. Several studies have shown that conversion to another bariatric procedure is safe with low morbidity (1.1%) and mortality (<1%) [24,25]. Both conversion procedures have similar complication rates, hospital stay and early weight loss [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study was published in 2018 demonstrated overall complications among sleeve gastrectomy after adjustable gastric band failure was only 1.1%. 11 The efficiency of LSG as a revision surgery following poor results after LAGB was assessd by Acholonu. It's possible to employ it as a follow-up operation after LAGB, although it appears to have more difficulties than the initial procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Trata-se de uma técnica realizada por via laparoscópica que pode ser reversível, porém apresenta um alto grau de insucesso, normalmente ocorrendo uma segunda abordagem cirúrgica. Esta técnica apresenta um melhor resultado quando acompanhada de mudança no estilo de vida e apresenta uma baixa mortalidade 5,6 .…”
Section: Banda Gástrica Ajustávelunclassified